Rumen Microbiota Distribution Analyzed by High-Throughput Sequencing After Oral Doxycycline Administration in Beef Cattle - Chen, Fengmei; Cheng, Guangmin; Xu, Yulin; Wang, Yunzhou; Xia, Qingxiang; Hu, Shilin (Frontiers in Veterinary Science, 2020)
The beef cattle rumen is a diverse microbial ecosystem that is essential for the host to digest food and support growth. The importance of the rumen microbiota (RM) is also widely recognized for its critical roles in animal metabolism, immunity, and health. The level of health can be reflected by dynamic RM distribution. In this study, high-throughput sequencing of the bacterial 16S rRNA gene was used to compare microbial populations from rumens in beef cattle with or without doxycycline treatment to assess dynamic microbiotic shifts following antibiotic administration. Doxycyline-treated beef cattle had lower species richness and bacterial diversity than those without doxycycline based on the results of the operational taxonomic unit analysis and calculations of alpha and beta diversity. Bacteroidetes was the most dominant phylum in rumen samples without doxycycline, while Proteobacteria was the governing phylum in the presence of doxycycline. On the family level, the top three predominant populations in group qlqlwy were Prevotellaceae, Lachnospiraceae, and Ruminococcaceae, compared to Xanthomonadaceae, Prevotellaceae and Rikenellaceae in group qlhlwy. At the genus level, the top predominant population in group qlqlwy was unidentified_Prevotellaceae. However, in group qlhlwy, the top predominant population was Stenotrophomonas. The results revealed significant RM differences in beef cattle with or without doxycycline. Oral doxycycline may induce RM composition differences, and bacterial richness may also influence corresponding changes that could guide antibiotic use in adult ruminants. This study is the first to assess bacterial flora distribution in beef cattle rumen before and after doxycycline administration.